Picornaviruses and nuclear functions: targeting a cellular compartment distinct from the replication site of a positive-strand RNA virus - Flather, Dylan; Semler, Bert L. (Frontiers in Microbiology, 2015)
The compartmentalization of DNA replication and gene transcription in the nucleus and protein production in the cytoplasm is a defining feature of eukaryotic cells. The nucleus functions to maintain the integrity of the nuclear genome of the cell and to control gene expression based on intracellular and environmental signals received through the cytoplasm. The spatial separation of the major processes that lead to the expression of protein-coding genes establishes the necessity of a transport network to allow biomolecules to translocate between these two regions of the cell. The nucleocytoplasmic transport network is therefore essential for regulating normal cellular functioning. The Picornaviridae virus family is one of many viral families that disrupt the nucleocytoplasmic trafficking of cells to promote viral replication. Picornaviruses contain positive-sense, single-stranded RNA genomes and replicate in the cytoplasm of infected cells. As a result of the limited coding capacity of these viruses, cellular proteins are required by these intracellular parasites for both translation and genomic RNA replication. Being of messenger RNA polarity, a picornavirus genome can immediately be translated upon entering the cell cytoplasm. However, the replication of viral RNA requires the activity of RNA-binding proteins, many of which function in host gene expression, and are consequently localized to the nucleus. As a result, picornaviruses disrupt nucleocytoplasmic trafficking to exploit protein functions normally localized to a different cellular compartment from which they translate their genome to facilitate efficient replication. Furthermore, picornavirus proteins are also known to enter the nucleus of infected cells to limit host-cell transcription and down-regulate innate antiviral responses. The interactions of picornavirus proteins and host-cell nuclei are extensive, required for a productive infection, and are the focus of this review.